Investigating the magnetic fluid characteristics in low concentration solutions to enhance harmonics generation - Mohd Mawardi, Saari; Saifudin, Razali; Amir Izzani, Mohamed; Hamdan, Daniyal; Hamzah, Ahmad; Sutjipto, Agus Geter Edy; Nazatul Sharreena, Suhaimi; Muhammad Hafiz, Mazwir (2016)
The generation of harmonics during application of AC and DC magnetic fields to multicore iron oxide particles in low concentration solutions was studied based on magnetization curve and harmonics response of the nanoparticles in low concentration solutions. As a first step, the distribution of particle size was analyzed using a Non- Negative Inversion Method to investigate the relation between particle size and diamagnetic contribution of liquid carrier. The harmonics of nanoparticle solutions was evaluated using a highly sensitive AC susceptometer, which was developed during this research period. Based on harmonics response, distribution of particle size, and the derived models of AC susceptibility response, the fundamental harmonic generation was affected by the diamagnetic contribution when the iron concentration was lower than 6 microg/ml..